AKTUALISASI SATUAN PENGAWASAN INTERN (SPI) DALAM MENINGKATKAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAN ASET (STUDY KASUS : UNIVERSITAS NEGERI SURABAYA) - IZZATUR RACHMAN, WILDAN (Jurnal Akuntansi AKUNESA, 2016)
This research aims to find out if the Intern Controlling Unit in realizing the accountability financial management and asset management at the State University of Surabaya. This research is a descriptive qualitative research in methods of data retrieval through interview, observation, and document tracking  audit results of SPI and related documents of research. As for the object of research to perform data retrieval on the head of the Department Financial Officer (Treasurer the Centre of Unesa), head of Unesa Supplies (UHTP), Chairman and Secretary of the Intern Controlling Unit  at the State University of Surabaya. With the SPI at State University of Surabaya can detect the occurrence of perversion and disobedience against the provisions of the applicable legislation. Implementation of the Implementation of the monitoring conducted by SPI to process financial management and asset management from planning to reporting easier for leaders to evaluate the policy and improve internal control system in the management of financial and asset management. The results of this study showed a aktualiasasi SPI in realizing increased accountability in the management of finance and asset management at the State University of Surabaya.   Keywords: Actualization Internal Controling Unit, Accountability Financial Management, Accountability Asset Management